FIRM SURVIVAL IN ENVIRONMENTAL TURBULENCE: DIGITAL STARTUP RESPONSE TO COVID-19 - Achmad Farid; Anton Wachidin Widjaja (President University, 2021)
The Covid-19 outbreak has resulted in changes and uncertainties in a dynamic business environment, which is indicated as Environmental Turbulence. The situation has an impact on the current performance of SMEs, including in the Greater Jakarta Area, Indonesia, where the startup population reaches more than 300 businesses. The purpose of this study is to investigate the indirect impact of Entrepreneurial Orientation (EO) as an antecedent and also the direct impact of Market Orientation (MO) and Digital Platform Capability (DPC) moderated by Environmental Turbulence on Firm survival which is one type of performance. No performance can be expected in this situation except for survival. Previous researches have shown that EO and MO can have a significant impact on performance in SMEs’ context. We try to combine EO and MO with DPC as one strategy that also enables Startup to survive in environmental turbulence. Regarding the objectives and research model, this research is a conceptual paper which the researcher will be proposing and will empirically validate the survey data for 120 Digital Startup in the Greater Jakarta Area, Indonesia with the SEM PLS method. This research is trying to give the literature contribution on how to digital startup can survive in environmental turbulence by analyzing the influence of EO, MO, and DPC on firm survival.Keywords: Entrepreneurial Orientation, Market Orientation, Digital Platform Capability, Firm Survival, Environmental Turbulence.